Effects of crack orientation and heat treatment on fatigue-crack-growth behavior of AM 17-4 PH stainless steel. (1st March 2020) - Yadollahi, Aref; Mahmoudi, Mohamad; Elwany, Alaa; Doude, Haley; Bian, Linkan; Newman, James C.
Highlights: Effects of heat treatment and crack orientation on FCG behavior of AM 17-4 PH SS. FCG test results for AM 17-4 PH SS over a wide range of stress ratios and rates. New methods to generate more accurate crack-growth rates in the near-threshold regime. Microstructural characterization and failure mechanism of AM 17-4 PH SS. Abstract: The effects of heat treatment and crack orientation on fatigue-crack-growth (FCG) behavior of 17-4 precipitation hardening (PH) stainless steel (SS) fabricated via a laser powder bed fusion (LPBF) additive manufacturing (AM) system were investigated. Accurate representation of FCG thresholds, the region defining crack growth as either very slow or nonexistent, is extremely important in adoption of AM for structural applications. In this study, new methods called compression pre-cracking constant-amplitude (CPCA) and load-reduction (CPLR) were used to generate FCG rate data in the near-threshold (low-rate) regime using non-standard or modified compact specimens. For comparison, the current ASTM load-reduction (LR) method was also used. Results indicate that FCG behavior of AM 17-4 PH SS in the Paris regime was comparable to that of wrought 17-4 PH SS in the peak-age condition. Although the post-manufacturing heat treatment was found to be necessary in order to improve tensile strength of this alloy, the results of this study indicate that this particular heat treatment process had no influence on FCG behavior of LPBF 17-4 PH SS. The effect of crack orientation with respect to the build direction however was evident. FCG rates were slightly lower for specimens with a crack parallel to the build direction (i.e. longitudinal crack) in the Paris regime as compared to that of specimens with a perpendicular crack (i.e. transverse crack). The near-threshold FCG behavior for specimens with a longitudinal crack did not show the usual stress ratio ( R )-shift from low to high R . The low- R data was vastly different than the data generated using the specimens with a transverse crack. Our results also imply that both the current ASTM standard LR method and the new CPLR method induce remote closure, which prematurely slows down crack growth and produces an abnormally high threshold.